THE ECONOMIC IMPACT OF SAND MINING ON COASTAL COMMUNITIES IN PANTAI HARAPAN VILLAGE, LINGGA REGENCY - Fauzy, Fauzy; Hafsar, Khairul; Tetty, Tetty (Politeknik Kelautan dan Perikanan Dumai, 2025)
Sand mining activities can absorb labor and also be a source of pollution that causes damage in the form of mud and turbidity. Since its establishment in 2019 to 2024, there has been no clarity regarding the mining permits carried out. Sand mining activities involve taking river sand and causing environmental impacts that result in river water pollution around the mine and even into the sea. The purpose of the study was to calculate the income of coastal communities before and after sand mining, calculate the percentage change in income of coastal communities due to sand mining and calculate the percentage of labor absorption created from sand mining activities in Pantai Harapan Village, Lingga Regency. The research was conducted in March-April 2024 in Pantai Harapan Village, Selayar District using a quantitative descriptive method. The number of samples in the study was 42 respondents. The research uses income analysis, percentage changes in income and labor absorption with existing formulas using Microsoft Excel software. The results of the study showed that the average change in community income before mining was IDR 24,517,452/year, after mining it was IDR 37,297,230/year. The percentage change in income of the people of Pantai Harapan Village after mining is 20%. The absorption of labor due to sand mining is 4%.